Democratic Republic of Timor-Leste Public Expenditure Review : Infrastructure - World Bank (Washington, DC, 2015)
The Timor-Leste Government’s 2011-2013 strategic development plan (SDP) outlines its plan for achieving upper-middle income country status, with a secure, well-educated, and healthy population, by 2030. It argues that the four key national attributes of political will, economic potential, national integration, and a dynamic population will underpin the achievement of this vision. The development of infrastructure is a core pillar of the SDP. Thus, the SDP outlines specific plans for a number of large construction projects for the development of roads and bridges, water and sanitation facilities, electrical power generation facilities, telecommunications, and ports. The SDP recognizes that Timor-Leste currently lacks the core infrastructure required to support a modern and productive economy. According to the SDP, government spending on infrastructure will drive high, double-digit rates of economic growth in the short and medium term, contributing to a rate of growth of 8 percent by 2020. The SDP also emphasizes the construction of infrastructure as a means to achieve its stated goals in the pillars of economic development, notably agriculture, and the development of social capital. The SDP commits the government to a significant school building program and to the expansion and rehabilitation of health facilities such as local clinics and hospitals.